Hypoxia and lymphangiogenesis in tumor microenvironment and metastasis - Ji, Rui-Cheng (Cancer letters, 2014)
Hypoxia and lymphangiogenesis are closely related processes that play a pivotal role in tumor invasion and metastasis. Intratumoral hypoxia is exacerbated as a result of oxygen consumption by rapidly proliferating tumor cells, insufficient blood supply and poor lymph drainage. Hypoxia induces functional responses in lymphatic endothelial cells (LECs), including cell proliferation and migration. Multiple factors (e.g., ET-1, AP-1, C/EBP-δ, EGR-1, NF-κB, and MIF) are involved in the events of hypoxia-induced lymphangiogenesis. Among them, HIF-1α is known to be the master regulator of cellular oxygen homeostasis, mediating transcriptional activation of lymphangiogenesis via regulation of signaling cascades like VEGF-A/-C/-D, TGF-β and Prox-1 in experimental and human tumors. Although the underlying molecular mechanisms remain incompletely elucidated, the investigation of lymphangiogenesis in hypoxic conditions may provide insight into potential therapeutic targets for lymphatic metastasis.